2019
DOI: 10.21608/jhiph.2019.49259
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Emotional Problems among Adolescent Students

Abstract: Background & Objective(s): Emotional and behavioral problems among adolescents represent a considerable public health problem in developing countries. These problems are considered a source of stress for adolescents as well as their families, schools and community. Emotional health and wellbeing of young people have implications on their self-esteem, behavior, school attendance, educational achievement, social cohesion and future health and life chances. To estimate the prevalence of emotional and behavioral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“… 28 Adolescents whose fathers had only completed junior high school showed the highest prevalence in this study of conduct problems, which was consistent with findings from Egypt and China of higher SDQ subscale scores for adolescents with low paternal education levels. 6 , 7 Hu et al 29 also observed this correlation in a study in China, that is, people with high education have better job opportunities than people with low education. In addition, a study in the United States of America (USA) found that compared with high-income families, the hospitalization rate of children with conduct disorders in low-income families is 1.5 times higher.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“… 28 Adolescents whose fathers had only completed junior high school showed the highest prevalence in this study of conduct problems, which was consistent with findings from Egypt and China of higher SDQ subscale scores for adolescents with low paternal education levels. 6 , 7 Hu et al 29 also observed this correlation in a study in China, that is, people with high education have better job opportunities than people with low education. In addition, a study in the United States of America (USA) found that compared with high-income families, the hospitalization rate of children with conduct disorders in low-income families is 1.5 times higher.…”
Section: Discussionmentioning
confidence: 75%
“…The young people in this study whose mothers had low education showed a higher prevalence of abnormal mental health scores, consistent with multiple earlier previous findings of higher SDQ subscale scores among teens with low maternal education levels. 6 Based on this, the study also reported that parents with higher education are more likely to exhibit active parenting behavior, and this association is partly due to their increased ability and knowledge to obtain more resources. 28 Adolescents whose fathers had only completed junior high school showed the highest prevalence in this study of conduct problems, which was consistent with findings from Egypt and China of higher SDQ subscale scores for adolescents with low paternal education levels.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The reason for which could be the obvious depression, anxiety, stress observed by the both at-risk populations due to the challenges of transition from one age group to the next one (Collins & Munoz-Solomando, 2018;Nebhinani& Jain, 2019). The major challenges for adolescents constitute of bodily changes (i.e., development of secondary sex characteristics) (Kar, Choudhury, & Singh, 2015;McAteer et al, 2017;Pringle et al, 2016), peer group pressure Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 25 July 2020 doi:10.20944/preprints202007.0620.v1 (Moldes, Biton, Gonzaga, & Moneva, 2019;Singh, 2017;Tripathy, 2018), behavioral and emotional disturbances (Borba & Marin, 2018;Osman, Khalaf, Omar, & Ismail, 2019;Williams, Scott, & Aarons, 2018). The young adults, on the other hand, face challenges of transition from adolescent to adulthood (Fegert, Hauth, Banaschewski, & Freyberger, 2016;Switek & Easterlin, 2018), financial pressure (Dewilde, Hubers, & Coulter, 2018;Lennartz, Arundel, & Ronald, 2016;Stein et al, 2013), conflict at the stage of isolation vs. intimacy (Mackinnon, De Pasquale,, & Pratt, 2016), personal development (Bonnie et al, 2015), and change in outlook towards life (Switek & Easterlin, 2018).…”
Section: Introductionmentioning
confidence: 99%